KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS MANAGEMENT OF SICKLE CELL DISEASE AMONG CARETAKERS OF SICKLERS AT PAEDIATRIC WARD IN MBALE RRH. A CROSS-SECTIONAL STUDY. - Namajja , Deborah; Kasujja, Henry (Student’s Journal of Health Research Africa, 2023)
Introduction: Purpose of the study: The study aims at assessing the knowledge, attitude, and practices towards the management of sickle cell disease among caretakers of sicklers at the pediatric ward in Mbale Regional Referral Hospital. Methods: A cross-sectional study that employed a simple random probability sampling technique to select 100 caretakers of sicklers at the pediatric ward to participate in the study. The questionnaire method was used in the collection of data. Results: 79(79%) of the caretakers reported pallor as a sign of SCD that requires immediate attention, 71(71%) knew blood transfusion as a treatment option for SCD, and 76(76%) knew the child should drink 10-15 glasses of water per day as a precaution to be taken at home for the child to live healthy. However, the majority of the participants 62(62%) did not know the complications of SCD if not managed well. 86(86%) preferred taking the child to a health facility when they get a sickle cell crisis, 82(82%) agreed that a child with SCD should get regular treatments and 82(82%) agreed that a child with SCD should get regular treatments. 43(43%) reported giving the child painkillers when a child gets a painful crisis and 38(38%) reported ensuring the child drinks enough water to prevent a sickle cell crisis. Conclusions: Given the above results, most of the respondents had good knowledge, a positive attitude, and poor practices towards the management of SCD. Recommendations. Health workers at Mbale regional referral pediatric unit should offer continuous health education to caretakers to improve their practices towards the management of SCD. The Ministry of Health should introduce a universal newborn screening program for early diagnosis and initiation of comprehensive SCD care for children. Caretakers should adhere to the recommended home-based care immediately after the child is diagnosed to prevent complications.